Self-efficacy dan Hasil Belajar Siswa dalam Pembelajaran Problem Based Learning (PBL) dengan Media PhET - Singgih Bektiarso; Ninik Megawati; Sri Handono Budi Prastowo (Universitas Sultan Ageng Tirtayasa, 2022)
This research aimed to examine the application of the problem-based learning model with PhET to students' self-efficacy and physics learning outcomes at SMA Negeri Pakusari, especially in light waves. This research is an experimental study with a pretest and posttest control group design. Determination of the sample using purposive sampling technique and obtained samples, namely the control and experimental classes. Self-efficacy data was collected through a questionnaire consisting of 9 statements, while the learning outcomes data were viewed from the cognitive domain through tests in the form of pretest and posttest. The test consists of eight multiple choice questions and four essay questions. Analysis of self-efficacy data and learning outcomes using the T-test sig value. Obtained is less than 0.05. Thus, it is concluded that there is a significant influence in applying problem-based learning models with PhET media on self-efficacy and student learning outcomes in high school